Assessment of Urban Flood Problems in Mandalay - Ingyin Mar, Tint; Aye, Nilar (AI Society & STMIK Indonesia, 2024)
Urban flooding poses significant challenges to Mandalay, exacerbated by rapid urbanization and inadequate drainage infrastructure. This study assesses urban flood problems in three basins such as Shwe Kyin, Thin Ga Zar, and Pa Yan Taw using the Storm Water Management Model (SWMM) under return periods of 10, 30, and 50 years. The required parameters, including rainfall patterns, land use, hydrologic soil group and drainage network characteristics, were used to simulate runoff and flood dynamics. After simulation, the maximum flood depths were evaluated for the three basins at specific time intervals. The results indicated that the maximum flood depth was observed as 0.1 m for Shwe Kyin Basin, 0.5 m for Thin Ga Zar Basin, and 0.6 m for Pa Yan Taw Basin, respectively. These findings emphasized a valuable reference for urban planning and disaster management strategies.